Similarities between the lipid proile of Mexican patients with lupus and the general population - Colunga Pedraza, Iris Jazmín; Galarza Delgado, Dionicio Ángel; Góngora Rivera, Juan Fernando; Esquivel Valerio, Jorge Antonio; Carrillo Palacios, R. A.; Segarra Linares, S.; Sánchez Núñez, A. L.; Colunga Pedraza, Perla Rocío; Vega Morales, David; Garza Elizondo, Mario Alberto (UANL. Facultad de Medicina, 2014)
Premature cardiovascular events have been observed in systemic lupus erythematosus (SLE) patients, but the reason for this accelerated process is still debatable; although traditional risk factors are more prevalent in such patients than in the general population, the do not seem to fully explain that enhanced risk. One of the most important conditions is a proatherogenic lipid proile. There is not enough data about it in Mexican SLE patients. Objective: To establish the differences in the lipid proiles between Mexican patients with SLE and the general population. Material and methods: Observational, transversal, descriptive and comparative study, between SLE patients and age-sex-matched healthy volunteers. We performed a full lipid proile (by spectrophotometry) 14 hours of fast. The results obtained were analyzed by the statistical program SPSS® Statistics version 17. Results: We studied the full lipid proiles of 138 subjects, 69 with a diagnosis of SLE and 69 agesex- matched healthy volunteers; 95.7% were females and 4.3% males. Average age was 30 years; average body mass index (BMI) 25.96 ± 5.96 kg/m² in SLE patients and 26.72 ± 4.36 kg/m² in the control group (p = 0.396). Average of total cholesterol 156 mg/dl in the SLE patients and 169.4 mg/dl in the control group (p =0.028); average of low density lipoprotein (LDL) cholesterol 85.27 mg/dl in the SLE patients and 97.57 mg/dl in the control group (p = 0.023). Conclusions: We did not ind statistical differences in the lipid proiles among patients and healthy volunteers, which could explain increased cardiovascular morbidity and mortality observed in SLE patients